Pemanfaatan Teori Semantik dalam Penerjemahan Ayat Al-Quran: The Use of Semantic TheoryIn Translation of Verses of Al-Quran - Nurhayati, Ratna (Balai Bahasa Provinsi Papua, 2022)
The Holy Qur'an is an authoritative book that has the authority to govern or make rules that adherents must implement. Because not all religious adherents understand the source language (BSu) in the scriptures, it is necessary to translate the scriptures into the target language (BSa). In linguistic studies, especially semantics is able to bridge the study of translation and the study of the meaning of language in order to produce good translations. In translation, there are six problematic meanings, namely lexical meaning, grammatical meaning, textual meaning, contextual meaning, idiomatic meaning, and socio-cultural meaning. Therefore, a translator, especially an authoritative text translator needs to understand linguistic studies, especially semantic in order to be able to produce quality translations.